2017
DOI: 10.1111/1346-8138.13852
|View full text |Cite
|
Sign up to set email alerts
|

Salivary chromogranin A levels correlate with disease severity but do not reflect anxiety or personality of adult patients with atopic dermatitis

Abstract: Stress-induced scratching is an issue in patients with adult atopic dermatitis (AD). Although itching and stress are believed to be intimately related, no objective index is available; therefore, most evaluations are subjective. Using saliva, which is easily collected, we investigated the degree to which AD severity and patient stress levels are reflected in stress proteins in the saliva. Here, we evaluated the severity (Scoring Atopic Dermatitis [SCORAD] score), stress (State-Trait Anxiety Index [STAI] score)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 19 publications
0
19
0
6
Order By: Relevance
“…The study included 30 patients with AD (19 men, 11 women; mean age, 32.71 years; range, 17–57) who were examined in the Department of Dermatology, Shimane University Hospital, between April 2015 and May 2017, and consented to participate in this study. The patients who participated in this experiment met the diagnostic criteria of AD proposed by the Ministry of Health, Labor and Welfare Research Group . Patient data was anonymized prior to the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included 30 patients with AD (19 men, 11 women; mean age, 32.71 years; range, 17–57) who were examined in the Department of Dermatology, Shimane University Hospital, between April 2015 and May 2017, and consented to participate in this study. The patients who participated in this experiment met the diagnostic criteria of AD proposed by the Ministry of Health, Labor and Welfare Research Group . Patient data was anonymized prior to the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Salivary CgA is attracting attention as a new indicator of psychological stress. We previously reported that the CgA per protein in saliva correlates with the severity of AD …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a link between stress and AD severity . Chromogranin A in saliva as a stress marker is well known and has been found to be related to stress and the severity of AD . Additionally, changes in the subjective severity scores have been found to be correlated with changes in salivary CgA .…”
Section: Discussionmentioning
confidence: 99%
“…They consented to participate in this study by opt‐out method. The patients who participated in this experiment met the diagnostic criteria for AD proposed by the Ministry of Health, Labour, and Welfare Research Group . Patient data were anonymized prior to the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…8,9 Their stress levels are also very high. 10 Atopic dermatitis is more frequent in childhood, especially in the first five years of life. 11,12 The prevalence or incidence of AD in the first five years of childhood is 10%-16.5% and is generally considered to be increasing worldwide, at least from the 1980s to early 2000s.…”
Section: Introductionmentioning
confidence: 99%